Gender dan Pembagian Kerja Rumah Tangga Permeabel Kebahagiaan Suami-Isteri (Kajian Dampak Covid-19 Pada Keluarga Hunian Tetap “Dongkelsari” Gungan Wukirsari Sleman) - Leslie Retno Angeningsih, Agustinus Bima Nugraha (Jurnal Masyarakat dan Desa, 2022)
This study aims to examine how gender and the division of household chores permeable husband-wife happiness, the 2010 Merapi Eruption victims, living in Dongkelsari, a permanent relocation, and now are facing the impact of Covid-19. The survey was conducted on 90 respondents, who were randomly selected. Data were collected through observation, questionnaires, interviews, and documentation. They were analyzed using binary logistic regression. The results showed that four household chores permeable husband-wife happiness, namely: preparing breakfast by the wife who used to work, 11 years and above of marital age, owning goats, land, chickens, TV, cellphone, motorcycle, family members more than five, high incomes, have cars, jewelry, savings, and now being housewives tend to be less happy. Cleaning the house by a wife who owns a motorcycle, age is over 31 years old, has goats, savings, higher education, high income, refrigerator, and cow livestock tends to be happy. Doing laundry by husband and wife tends to make his/her happy. Fixing the house by a husband-wife who owns poultry tends to be unhappy. Spouses with 4 or more children tend to be less happy. Wives have no land but have bicycles and motorcycles tend to be happy. Overall, wives tend to be more persistent in struggling to deal with the impact of Covid-19 for the sake of their families than husbands. This situation should be a lesson on how important gender equality is for husband-wife happiness